2010
DOI: 10.2177/jsci.33.142
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of interstitial pneumonia and pneumomediastinum associated with polymyositis during pregnancy with a combination of cyclophosphamide and tacrolimus : A case report

Abstract: A 30-year-old pregnant woman experienced mild dyspnea in April 2009. She complained of mild myalgia and was subsequently admitted to our hospital in June 2009 because of worsening dyspnea. Physical examination revealed fine crackles in the lower lung field, but no eruptions externally. Laboratory findings revealed elevated serum levels of myogenic enzymes (aldolase, 17.6 IU/l and myoglobin, 247.2 ng/ml) and positive titers for the anti-Jo-1 antibody and hypoxia (PaO(2), 79.4 Torr). The chest radiograph reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In another case report, a pregnant woman at 16 weeks of gestation had developed IP preceding anti Jo-1 positive ASS, and was treated with a combination of steroid pulse therapy and tacrolimus. The fetus did not survive since it was too small, and the maternal condition deteriorated (26). To the best of our knowledge, the present case study is the first reported case of a patient having been diagnosed with anti-MDA5-positive RP-ILD complicated with CADM.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In another case report, a pregnant woman at 16 weeks of gestation had developed IP preceding anti Jo-1 positive ASS, and was treated with a combination of steroid pulse therapy and tacrolimus. The fetus did not survive since it was too small, and the maternal condition deteriorated (26). To the best of our knowledge, the present case study is the first reported case of a patient having been diagnosed with anti-MDA5-positive RP-ILD complicated with CADM.…”
Section: Discussionmentioning
confidence: 75%
“…Examples of clinical case studies for treating pregnant patients with DM or PM, especially CADM, are relatively rare, and case studies of a similar nature that we were able to identify are shown in supplementary material (18,(26)(27)(28). Tomohiro et al (18).…”
Section: Discussionmentioning
confidence: 79%
“…It should be noted that the use of immunosuppressants for the treatment of IP does not ensure rapid improvement in patient condition. In a similar case report, a pregnant woman at 16 weeks of gestation had developed IP preceding PM and was treated with a combination of steroid pulse therapy and tacrolimus [ 11 ]. Due to that patient's worsening respiratory condition, the pregnancy was terminated in the 21st week of gestation to save the mother.…”
Section: Discussionmentioning
confidence: 99%
“…6 The most frequently mentioned complication of DM/PM was interstitial lung disease. [19][20][21][22][23] The rate of cesarean delivery ranged from 23.3% 6 to 88.2% 5 (Supplementary Tables S1 and S2).…”
Section: Pregnancy In Dm/pmmentioning
confidence: 99%